Research Data: A Public Good or a Private Asset? - Tadeu Fernando Nogueira; Trude Eikebrokk; Laila Økdal Aksetøy (Liber Quarterly: The Journal of European Research Libraries)
This article is concerned with the issue of how Research Performing Organizations can balance the market and non-market values of the research data they hold. To address this issue, we adopt the lenses of the Resource Based View and Open Science and explore the interplay between them. In doing so, this article addresses the question of whether it is possible to achieve a balance between research data as a public good and as a private asset and if so, how. Of particular interest are Research Performing Organizations in the institute sector that operate under both market and non-market logics, which have implications for how they govern their research data. From the discussions undertaken in the article, one of the main conclusions is that Research Performing Organizations may benefit from adopting a research data governance model that captures both the economic and societal values of research data. They could do so, for instance, by developing an integrative institutional policy and by actively using data management plans to evaluate the value of the data produced in research projects.